From Supersaturated Drug Delivery Systems to the Rising Era of Pediatric Formulations - Charkoftaki, G.; Valsami, G.; Macheras, P. (CHEMICAL AND BIOCHEMICAL ENGINEERING QUARTERLY, 2012)
The number of options available to drug discovery scientists to enhance the solubility of poorly soluble compounds by conventional formulation approaches is limited. In most cases, drug formulation is oriented toward the creation of a supersaturated solution upon contact with aqueous environment, often combined with solubilizing agents and precipitation inhibitors. The most popular formulations for achieving this target are the lipid-based formulations called self-emulsifying and self-microemulsifying drug delivery systems, SEDDS and SMEDDS, respectively. They offer enhanced absorption and hence enhanced oral bioavailability of lipophilic drugs, presenting the drug in solubilized form in vivo, avoiding dissolution, which can be the rate limiting step in drug absorption for sparingly soluble drugs. The production of high energy or rapid dissolving solid state formulations using drug particle engineering to enhance drug solubility and bioavailability is also applied. These formulations include solid dispersions, nanoparticles, co-ground mixtures etc. Furthermore, the development of prodrugs is also a useful strategy to improve the physicochemical, biopharmaceutical or pharmacokinetic properties of pharmacologically potent compounds, and thereby increase the developability and usefulness of a potential drug. Up to now, most medications were made for adults and children's requirements were not taken into account. Since the recent adoption of Paediatric Regulations in the U.S. and E.U., there is a greater demand for age-appropriate medicines for children. The challenges in paediatric formulation development are mostly associated with the difficulty in defining design requirements for the intended dosage form that is most appropriate for the target patient population, due to the diversity of the paediatric population (range of ages, physical size and capabilities) that varies significantly from birth to age 12 yrs old along with the dosage flexibility. The last years there has been an effort to develop solid paediatric formulations that deliver the appropriate dose in a ``user friendly{''} way and to find alternative drug delivery vehicles, such as mini-tablets, dairy products, and new taste masking techniques in order to improve drug acceptability. In addition, alternative routes of administration have been proposed such as inhalation and nasal administration.
Keywords: Dissolution; Drug Delivery Systems; pediatric formulations; Solubility; Supersaturation